IMPROVING LITERACY THROUGH TECHNOLOGY FOR YOUNG LEARNERS - Zananda, Tiray Febria (Enrich: Jurnal Pendidikan, Bahasa, Sastra dan Linguistik, 2024)
Technology used to literacy to arrange the class is just one way to improve the teaching and learning process. Technology also brings its influences to the activities in the classroom during teaching and learning process. Teaching and learning process is complex and it needs some serious actions to make it success. Teaching and learning is a process that needs communication in delivering the material. Teachers can come up with different models in their teaching processes based on the prior observation related to cultural awareness and scientific designs through technology.